The Effect Of Using Semantic Mapping Strategy Toward Students Vocabulary Mastery At 8th Grade At Boarding School Jama’atul Mualimin - Rahmawati Rahmawati; Loli Safitri; Genta Sakti; Absharini Kardena (Jurnal Pendidikan dan Sastra Inggris, 2023)
This research was done to find out the effect of using semantic mapping toward students vocabulary mastery. It has been done at boarding school Jama‟atul Mualimin. Most of students still have limited vocabulary. The students were difficult remember vocabulary that they have learned, they cannot use correct vocabulary in sentences and the student were not interested in the classroom. In this research, the researcher used pre- experimental research with one group pretest and post-test design. The population of this research was the 8th grade students at boarding school Jama‟atul Mualimin which consisted of one class. The sample was taken by total sampling because the school just had one class. The sample of this research was the students of 8th grade which consisted of 19 students. The result of the research indicated the score of the student‟s posttest is higher than the score of pretest. The mean score of pretest is 47,31, where the mean score of students posttest is 88,26. It means that semantic mapping gave contribution toward student‟s vocabulary mastery. In addition to test the hypothesis, the t-obtained 18,17 while t-table on = 0,05 is 1.734. It means that the t-obtained is higher than t-table. In other words, the (Ha) was accepted and Ho was rejected. Which stated there was significant effect of using semantic mapping strategy at 8th grade at boarding school Jama‟atul Mualimin. It can be concluded that, using semantic mapping strategy gave significant effect of using semantic mapping strategy toward students vocabulary mastery.